Applied logistic regression. - Hosmer, David W.; Lemeshow, Stanley; Sturdivant, Rodney X. (Hoboken, New Jersey : Wiley, 2013)
"This Third Edition continues to focus on applications and interpretation of results from fitting regression models to categorical response variables"--
Keywords: Regression analysis; MATHEMATICS / Probability & Statistics / Regression Analysis